Silicon Carbide. Recent Major Advances - Choyke W. J.; Matsunami H.; Pensl G. (Advanced Texts in Physics)
Since the 1997 publication of Silicon Carbide A Review of Fundamental Questions and Applications to Current Device Technology, edited by Choyke et al., there has been impressive progress in both the fundamental and developmental aspects of the SiC field. So there is a growing need to update the scientific community on the important events in research and development since then. The editors have again gathered an outstanding team of the world's leading SiC researchers and design engineers to write on the most recent developments in SiC. The book is divided into five main categories: theory, crystal growth, characterization, processing and devices. Every attempt has been made to make the articles as up-to-date as possible and assure the highest standards of accuracy. As was the case for the earlier SiC book, many of the articles will be relevant a decade from now so that this book will take its place next to the earlier work as a permanent and essential reference volume.